DINAMIKA DAN KINERJA PEMERINTAHAN DESA DI KECAMATAN LAMBU KABUPATEN BIMA - Rifai Rifai (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
An important element in improving performance in the organization is the availability of quality human resources, productivity, having a high work ethic, and being able to make optimal contributions. In the Village Government environment, the Village Head and all Village Apparatus as executors of Village Government duties are expected to carry out village government duties properly in order to create the welfare and development of the people in the village. In increasing the capacity of Village Apparatus, the policy of the Naru Village Government to engage in this kind of activity is very important to follow. The dynamics of the Renda Village Government in Woha Sub-district are so dynamic that this is influenced by the dialectic of leadership or village heads who are in the process of reaching an educational point in understanding the management of village governance. The role of village government is a measure that states how far the target is determined in advance. In its development, most villages in Indonesia are essentially still the original legal community unit, based on customary law regulations. Keywords; Dinamika, Kinerja, dan Pemerintahan